Hydrogen energy systems for underwater applications. (26th May 2022) - Sezgin, Berna; Devrim, Yilser; Ozturk, Tayfur; Eroglu, Inci
Abstract: The most critical development in conventional underwater applications in recent years is to use hydrogen energy systems, including Air Independent Propulsion (AIP) systems. Proton Exchange Membrane (PEM) fuel cell-powered AIP systems increase interest worldwide. They offer many advantages such as longer endurance time without going to the surface for 2–3 weeks or without snorkeling with an average speed, perfectly silent operation, environmentally friendly process, high efficiency, and low thermal dissipation underwater. PEM fuel cells require a continuous source of hydrogen and oxygen as reactants to sustain a chemical reaction to produce electrical energy. Hydrogen storage is the critical challenge regarding the quality of supplied hydrogen, system weight, and volume. This paper reviewed hydrogen/oxygen storage preferences coupled with PEM Fuel Cell applications in the literature for unmanned underwater vehicles. Since underwater vehicles have different volume and weight requirements, no single hydrogen storage technique is the best for all underwater applications. Highlights: Hydrogen is the preferred fuel for underwater vehicles. Underwater vehicles use hydrogen energy systems having Air Independent Propulsion (AIP) systems. This paper review H2 /O2 storage preferences coupled with PEM Fuel Cell applications for unmanned underwater vehicles. Compressed, and metal hydride-based H2 storages are suitable for small to medium submarines.